Analisis Kualitas Air Isi Ulang Usaha Air Rebusan (UAR) Berdasarkan Standar Kesehatan di Kabupaten Merangin - Dewi Wira Trisenag; Ummi Kalsum; Rifli Rindes (Universitas Baiturrahim, 2023)
Enthusiasts for the refill drinkig water the Boiled Water Business (UAR) in several districts in Jambi Province are increasing. The quality of the water used is not guaranteed when compared to the Refill Drinking Water Depot (DAMIU) because there has never been a quality check and the form of supervision has not been officially legalized. The aim of the study was to analyze factors related to the quality of refilled water from UAR. The research method is mixed method. Primary data was collected in field and Labkesda Merangin district, secondary data from the Merangin District Health Office, the Central Statistics Agency, and Puskesmas in the Merangin District from April to August 2022. The population is the UAR depot in Merangin District totaling 38 samples. Interviews with questionnaires and field observations. The dependent variable is the physical and bacteriological quality of UAR refilled water, the independent variable is the aspect of the place, the aspect of the equipment, the source of raw water, the hygiene of the handlers and the guidance. Univariate and bivariate analysis using chi-square test, at 95% confidence level. The results of the study found aspects that did not meet the requirements for physical worthiness included: place (42.1%), handler hygiene (44.7%), equipment (36.8%), raw water (36.8%) and there were 55.3 % Undeveloped UAR. There is a relationship between aspects of equipment, raw water, handler hygiene and coaching with recycled water quality. It has not been proven that there is a relationship between the aspect of the place and the quality of the return water. The reason consumers choose UAR refilled water is because of the belief in water quality assurance and the hygiene of the handler. Boiled water business was chosen by UAR entrepreneurs because of the small capital, the amount of profit, high consumer demand and the ease of processing. It is hoped that in the future all parties in Merangin district, especially the government, can pay attention to this effort so that its quality is guaranteed.